Ways to harmonize the individual teacher in the future to pіdgotovki zberezheniyu and strengthening of occupational health (Pedagogy of Higher and Secondary Education, 2012)
Mieszko G. Ways to harmonize the individual teacher in the future to pіdgotovki zberezheniyu and strengthening of occupational health.The analysis of personality harmonization ways in future teacher in the context of her preparation to saving and improvement of professional health (the formation of individual style of pedagogical activity; the formation of positive and sanogenic thinking; actualization of spiritual and creative potential) has been carried out in the article.
Keywords: harmony and disharmony of a personality; harmonization of a future teacher’s personality; the ways of personality harmonization